LEGAL FRAMEWORK FOR THE E-HRYVNIA IN UKRAINE AS A MEANS OF REFORMING THE FINANCIAL SYSTEM - Устинова, Ірина; Пєсцов, Руслан (SWorldJournal, 2024)
Тhe article outlines the current global approaches to the introduction of electronic money arising from the objective grounds for the development of the financial system and financial control and virtual assets; the author describes the CBDC system develo